In Vitro Comparison of Antibacterial Efficacy of a New Irrigation Solution Containing Nanosilver with Sodium Hypochlorite and Chlorhexidine - Kangarlou, Ali; Tashfam, Babak; Naseri, Mandana; Dianat, Omid; Taheri, Soudabeh (Journal of Dental School, 2020)
Objective: Antibacterial properties of silver nanoparticles have recently come into the spotlight in endodontic therapy. This study was conducted aiming at comparing the antimicrobial activity of a new irrigation solution containing nanosilver particles with that of sodium hypochlorite and chlorhexidine against Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa and Candida albicans with direct culture technique. Methods: In this in vitro experimental study, Mueller Hinton agarmedium was prepared for cultivation of E. coli, C. albicans and P. aeruginosa species and Bile-Esculin agar culture medium was used for E. faecalis. Understudy irrigation solutions were chlorhexidine 2%, chlorhexidine 0.2%, sodium hypochlorite 5.25%, sodium hypochlorite 2.5%, sodium hypochlorite 1.125% and nanosilver solutions of 25, 50, 100, 150, 200, 400 and 4000 ppm. After preparation, the bacteria were exposed to these solutions and the culture media were stored in an incubator at 37°C for 24 hours.The diameter of growth inhibition zone was determined for different microbial species and data were analyzed using Kruskal-Wallis and Dunnett’s tests. Results: Significant differences were found between various irrigation solutions based on the diameter of growth inhibition zones for E. faecalis, E. coli, C. albicans and P. aeruginosa (P<0.0001). The greatest antimicrobial activity against microbial species belonged to sodium hypochlorite 5.25% and 2.5%. Silver nanoparticle solution had an acceptable antimicrobial activity in comparison to other solutions and its antimicrobial property constantly improved by increased concentration of Ag ions. The nanosilver containing irrigation solution at different concentrations up to 100 ppm did not show a significant difference with sodium hypochlorite 1.25% in terms of antimicrobial efficacy. Furthermore, the greatest antibacterial activity against P.aeruginosa was observed at different concentrations of nanosilver up to 100 ppm; whereas, chlorhexidine showed no antimicrobial activity against this microorganism. Conclusion: Based on the obtained results, nanosilver canal irrigation solution had a lower but acceptable antimicrobial activity against various bacterial species compared to conventional irrigation solutions. Therefore, once other characteristics of nanosilver are approved, further studies can be performed to improve its properties and use it as an alternative to conventional root canal irrigation solutions.